A Long Poem: Take Time to… - Friesen, Helen Lepp (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2020)
In “A Long Poem: Take Time to …”, I relate how the people on one city block engaged in a community based “long poem” art project during the Covid-19 pandemic. Arranged in two parts, this paper first looks at the literature on community art and its impact on personal and social health and wellbeing. Second, I describe how a street community art and poetry project led to social engagement, dialogue, healthy interaction, and good memories.